2022
DOI: 10.1242/dev.200538
|View full text |Cite
|
Sign up to set email alerts
|

Major transcriptomic, epigenetic and metabolic changes underlie the pluripotency continuum in rabbit preimplantation embryos

Abstract: Despite the growing interest in the rabbit model for developmental and stem cell biology, the characterization of embryos at the molecular level is still poorly documented. We conducted a transcriptome analysis of rabbit pre-implantation embryos from E2.7 (morula stage) to E6.6 (early primitive streak stage) using bulk and single-cell RNA-sequencing. In parallel, we studied oxidative phosphorylation and glycolysis and analysed active and repressive epigenetic modifications during blastocyst formation and expan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…Many of the selected genes have been demonstrated to support naïve pluripotency or facilitate the resetting of naïve-like features when overexpressed in mice and humans (Cartwright et al 2005;Ema et al 2008;Jiang et al 2008;Parisi et al 2008;Bourillot et al 2009;Guo et al 2009;Silva et al 2009;Guo and Smith 2010;Han et al 2010;Lee et al 2012;Nagamatsu et al 2012;Martello et al 2013;Tai and Ying 2013;Uranishi et al 2013;Stuart et al 2014;Takashima et al 2014;Qiu et al 2015;Pastor et al 2018;Festuccia et al 2021;Lea et al 2021). Our RNAseq analyses of rabbit embryos confirmed that all but one gene (GFI1) were expressed in the ICM/early epiblast of day 3 and 4 rabbit blastocysts (Bouchereau et al, 2022) (Fig. S2A).…”
Section: Cdna Library Screeningsupporting
confidence: 55%
“…Many of the selected genes have been demonstrated to support naïve pluripotency or facilitate the resetting of naïve-like features when overexpressed in mice and humans (Cartwright et al 2005;Ema et al 2008;Jiang et al 2008;Parisi et al 2008;Bourillot et al 2009;Guo et al 2009;Silva et al 2009;Guo and Smith 2010;Han et al 2010;Lee et al 2012;Nagamatsu et al 2012;Martello et al 2013;Tai and Ying 2013;Uranishi et al 2013;Stuart et al 2014;Takashima et al 2014;Qiu et al 2015;Pastor et al 2018;Festuccia et al 2021;Lea et al 2021). Our RNAseq analyses of rabbit embryos confirmed that all but one gene (GFI1) were expressed in the ICM/early epiblast of day 3 and 4 rabbit blastocysts (Bouchereau et al, 2022) (Fig. S2A).…”
Section: Cdna Library Screeningsupporting
confidence: 55%
“…The PGC states are associated with high expression levels of TFAP2C, SOX15, SOX17, CITED1, FOXA3, and NANOS3 ( Figure 7A ). Interestingly, SOX15 has been shown to be a primate and rabbit naïve pluripotency TF, though not in mouse 13,40 . Analysis of PS and nascent mesoderm TFs, clearly showed that PGCs from all embryonic stages do not upregulate most canonical TFs, such as T, EOMES, MIXL1, SNAI1 and HOXA1.…”
Section: Resultsmentioning
confidence: 99%
“…Single cell transcriptomics and multi-omics are recently being used to map transcriptional and chromatin states in early embryonic development 7,[12][13][14][15][16][17][18][19][20][21][22] . This resulted in comprehensive atlases that greatly enrich and refine previous imaging-based data by characterizing precisely transcriptional programs at high cellular resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work showed that mouse, rabbit, monkey and other species exhibit unique and shared developmental features in gene expression, epigenetic regulation, or as a whole with interspecies chimeras (Simerly et al, 2011; Okamoto et al, 2011; Wu et al, 2016; Nakamura et al, 2016; Fu et al, 2020; Bouchereau et al, 2022). However, little was known about cellular morphogenesis, cleavages, and their variabilities.…”
Section: Discussionmentioning
confidence: 99%